Synthesis and Functionalization of Triply Fused Porphyrin Dimers - RYAN, AOIFE; SENGE, MATHIAS (My University, 2013)
Current applications of porphyrins in medicine and optics, such as photodynamic therapy or nonlinear absorption, increasingly require the use of far-red absorbing dyes. Modifications to the porphyrin structure to accommodate these conditions can be achieved by extending the conjugation of the porphyrin ?-system, which will cause a bathochromic shift in the absorption spectrum. Thus, conjugated porphyrin oligomers have found widespread use. However, past synthetic strategies have mainly targeted symmetric porphyrin dimers, trimers, and oligomers which limit the practical use of such chromophores. To further extend the absorption profile, a series of symmetric and unsymmetric dimeric and oligomeric porphyrin ?-?, meso-meso, ??-?? triply-fused systems were synthesised via oxidative coupling methods. This required an analysis and optimization of the various synthetic strategies. These arrays exhibit a dramatic bathochromic shift into the nearinfrared region, many displaying absorption of greater than 1050 nm. Additionally, post-fusing chemical transformations, namely organolithium, cycloaddition and transition-metal catalysed reactions, at the meso- and ?- positions enables the fine-tuning of such arrays with the aim of enhancing the bathochromic shift and their potential optical applications.
PUBLISHED
Keywords: fused ring-systems; cycloaddition; C-C coupling; organolithium; porphyrinoids